Taxonomy of 'Euconnus complex'. Part X. Drastophus placed as a junior synonym of Tetramelus, and Smicrophus as a junior synonym of Napochus (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
Drastophus and Smicrophus were originally described as genera of Nearctic Scydmaeninae. Drastophus was later synonymized with Euconnus s. str., and subsequently resurrected as a subgenus of Euconnus. Smicrophus was also proposed as a genus, and later placed as a subgenus of Euconnus. However, examination of the type species of each subgenus in the present study led to different conclusions. Drastophus laevicollis differs only in minor details from the type species of Euconnus (Tetramelus), namely in a shorter head, and the pronotum not constricted near base and lacking the median longitudinal antebasal carina. These differences are not sufficient to maintain Drastophus as a separate subgenus, and this name is placed as a junior synonym of Tetramelus. Smicrophus leviceps, in turn, is very similar to Euconnus (Napochus); the only differences in relation to the type species of Napochus are the pronotum broadest slightly in front of base instead of at base, head lacking bristles, lateral antebasal pronotal pits shifted to a more submedian position, and a different shape of hypostomal ridges. Some of these characters were previously found to be variable within Napochus, and others are only minor differences that can also be interpreted as variability within a subgenus. Consequently, Smicrophus is placed as a junior synonym of Napochus.